Habitat Association and Conservation Status of the Endangered Giant Nuthatch (Sitta magna) in Thailand. (September 2018) - Techachoochert, Supatchaya; Gale, George A.; Khudamrongsawat, Jenjit; Round, Philip D.
The Giant Nuthatch Sitta magna is restricted to southwestern China, eastern Myanmar, and northern Thailand. Although globally endangered, most aspects of its ecology remain as yet unquantified. To assess its habitat associations and population size, we conducted point counts with playback at 42 sample points across 12 discrete historical and potential localities within its Thai range during October to November 2015. Eleven habitat variables were measured, including three site-level vegetation variables and eight landscape variables were assessed, using geographic information system land cover maps. N-mixture models were applied to estimate density and extrapolate the size of the population. The Giant Nuthatch was found at four localities (12 of the 42 sample points) at elevations between 1, 192 m and 1, 738 m. It was not detected at four historical Giant Nuthatch localities in protected areas. Abundance increased with increasing elevation, increasing proportion of evergreen forest, and greater distance from villages. We estimated that the Thai population of Giant Nuthatch was approximately 964 individuals based on an average density of 1.96 individuals/km 2 in approximately 491.8 km 2 of appropriate forest habitat at 1, 192 m to 1, 951 m elevation. This may be an overestimate because available forest cover maps and images do not distinguish between the characteristic, patchily distributed, lower montane open pine–oak forest association used by Giant Nuthatch and denser, closed-canopy forest. Although Thailand's Giant Nuthatch population may be better protected than those in adjoining countries, we suggest that it remains threatened by forest fragmentation and habitat degradation throughout its range. Further comprehensive research is needed to assess the status of the remaining global population and the reasons for its scarcity.